THE CHALLENGES OF INCIDENTAL FINDINGS AND OVERDIAGNOSIS IN RADIOLOGICAL PRACTICE - Nasser Ayed Salem Al-Sanani, Mohammaed Matleb Alanazi, Mufarreh Jubran Jubran Lughbi, Samar Ali Alhazmi, Saad Marui Mohammed Namis, Yahya Ahmed Yahya Mobarki; Ammash Ghali Alshammari, Abdulaziz Masad Alharbi, Yousef Mohammed Ahmed Al-Ahdal, Ahmed Mohammed Yousef Daghriry, Hamdan Ali Hamdan Alghamdi, Abdulaziz Mohammed A Almogamas; Aljawhara Saleh Aldalbahi, Abdulaziz Mohammed A Almogamas, Abdullah Nasser Alotaibi (Chelonian Research Foundation, 2022)
The objective of this research was to analyze the primary reasons that contribute to overimaging with X-ray, including self-referral, defensive medicine, and duplicate imaging procedures. Additionally, the study sought to highlight the ethical dilemma that arises from this issue. This study specifically examined the common causes of overdiagnosis, including the use of total-body CT scans for screening purposes in both public and private healthcare sectors. Additionally, it explored the selection of highly sensitive tests for various conditions such as pulmonary embolism, as well as the prevalence of ultrasound investigations for thyroid and prostate issues, and the use of MR examinations for musculoskeletal conditions. The immediate consequence of overdiagnosis and overimaging is an elevated risk of contrast media infusion, radiation damage, and increased expenses within the global healthcare system. The subject of the expenses associated with overdiagnosis is closely linked to the use of improper or inadequately justified imaging procedures. The ethical principles of trust and proper behavior are emphasized, since the primary ethical issues in radiology arise from the justification of medical exposures for patients during treatment. Close communication and collaboration among all doctors involved in patient care is crucial for determining the need for imaging examinations. This collaboration should carefully consider the potential drawbacks of ionizing radiation and the benefits it offers to the patient's overall treatment. Keywords: overimaging, overdiagnosis, radiological practice, X-ray, drawbacks of ionizing radiation, treatment.